Enhancing learning performance, attention, and meditation using a speech-to-text recognition application: evidence from multiple data sources. Issue 2 (17th February 2017) - Shadiev, Rustam; Wu, Ting-Ting; Huang, Yueh-Min
ABSTRACT: In this study, we provide STR-texts to non-native English speaking students during English lectures to facilitate learning, attention, and meditation. We carry out an experiment to test the feasibility of our approach. Our results show that the participants in the experimental group both outperform those in the control group on the post-tests and have higher attention and meditation. In addition, our results demonstrate that lower ability students who used STR-texts had higher learning performance, attention, and meditation than lower ability students in the control group. The results also show that attention and meditation are dynamic and change throughout the lectures. Furthermore, we found that attention trendlines have a negative slope, whereas meditation trendlines have a positive slope. Our results suggest that STR-texts are useful for non-native speaking students, especially those with lower language proficiency, and can enhance their comprehension of English lectures and also raise their attention and meditation. However, educators and researchers should keep in mind that interactive strategies need to be applied in order to maintain and even increase low proficiency student attention throughout the lectures.